Two Different Methods for Collection of Gingival Crevicular Blood to Estimate Random Blood Glucose Levels-A Comparative Study - Aarthi Nisha Venkatesan; Julius Amaldas; Mohan Valiathan; Vidya Jayaram; Parthiban Jayaraman (Wolters Kluwer Medknow Publications, 2018)
Aim and Objective: The present study was done to validate a reliable method for collection of gingival crevicular blood (GCB) and to use it as an alternative to routinely collected venous blood (VB) to estimate random blood glucose (RBS) levels. Materials and Methods: The study group comprised of 50 type 2 diabetic patients (n = 50), aged between 21 and 80 years attending the outpatient department of Sree Balaji Dental College and Hospital, Chennai. The study was a cross-sectional observational study that comprised of thorough clinical evaluation and estimation of RBS levels from GCB by two different methods, namely, direct glucometric method and collection through capillary tube method. Results: Out of the 50 patients, 27 (54%) were females and 23 (46%) were males. All the patients were among 20 to 70 years of age. On comparing the RBS levels from gingival crevicular obtained by direct intraoral method and capillary tube method, a statistically significant correlation of P < 0.05 was obtained proving statistically significant results. Further on comparing the results with VB glucose levels, there was no statistically significant difference found among the methods. Conclusion: The above study concludes that GCB collected by both capillary tube and direct intraoral method yielded almost similar blood glucose results which conclude either of the methods can be used to collect the sample.